Identifikasi Risiko Usahatani Padi di Kecamatan Kuta Baro Kabupaten Aceh Besar - Nurahmi Fajriah; Romano Romano; Irwan A kadir (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
Rice farming is an activity that is mostly carried out by rural communities in Aceh. Kuta Baro District is one of the sub-districts in Aceh Besar District and is the center of rice production but is inseparable from the various risks that threaten it. Rice farming does not always run smoothly, the declining level of farmers income can be caused by several risks thet often occur. Various risks faced by farmers in farming will be obstacle for farmers to increase production and farmers income. Considering the many risks faced by farmers and the limited resources and time that farmers have in overcoming the risks.so that no all risks can be handled properly, only some risks must be prioritizedbased on the sources of risks in rice farming. The purpose of this study is to map the most influential risks to rice farming and to determine the most important priority risks to rice farming in Kuta Baro District. The location of this research was chosen purposively, with a sampel of 30 farmers. The data used are primary data and secondary data. The methods and FMEA (Failure Mode and Effect Analysis) methods. The results showed that based on the calculation of the RPN (Risks  Priorty Number )then there are 5 risks out of 26 risks faced by farmers thet must be prioritized. The risks that must be prioritized first are drought whit an RPN value of 329,07, whater shortages and whater restrictions from irrigation with an RPN value of 290,67, the third is pest and disease attacks eith an RPN 16, the four uncertain climate changes with an RPN value. Of 156,67 and the price of expensive fertilizer with an RPfN value of 155,5.